Space use by female Greater Prairie-Chickens in response to wind energy development - Winder, V. L.; McNew, L. B.; Gregory, A. J.; Hunt, L. M.; Wisely, Samantha M.; Sandercock, Brett K. (My University, 2014)
Wind energy development is targeted to meet 20% of U.S. energy demand by 2030. In Kansas, optimal sites for wind energy development often overlap with preferred habitats of Greater Prairie-Chickens (Tympanuchus cupido), a lek-mating species of prairie grouse with declining populations. Our goal was to use movement data from radio telemetry to investigate patterns and drivers of seasonal space use by female prairie-chickens during pre- and post-construction periods at a wind energy facility in northcentral Kansas. We developed individual and population level resource utilization functions (RUFs) for four time periods: the 6-month breeding and nonbreeding seasons during the pre-construction stage (2007–2008; n = 28 and 14 females), and the same two seasons during a post-construction period (2009–2011; n = 102 and 37). RUFs relate non-uniform space use within a home range to landscape metrics in a multiple regression framework. We selected ten predictor variables that described land cover, habitat patchiness, anthropogenic disturbance, and social behavior of prairie-chickens. We documented two behavioral responses of females to wind energy development during the breeding season: (1) mean home range size increased approximately two-fold, and (2) space use had a positive relationship with distance to turbine, which indicated female avoidance of wind turbines. A parallel study of demographic rates in our study population found no negative effects of wind energy development on prairie-chicken fecundity or survival, but persistent avoidance of wind energy development could result in the local extirpation of prairie-chicken populations at our study site. Our primary ecological finding was that distance to lek was the strongest predictor of space use during all treatment periods, with relatively high use of areas at short distances from leks in 79% of female home ranges. Thus, lek site surveys should be effective for identifying prairie grouse habitat preferences and monitoring population dynamics when more intensive demographic studies are not feasible. Our study is the first application of resource utilization function techniques to a wildlife population in response to energy development, and our results provide new quantitative insights into the spatial ecology of an upland gamebird of conservation concern.
Keywords: Grouse; Home range; Landscape metrics; Lek; Northcentral Kansas; Tympanuchus cupido; Resource utilization function; Wind turbine; Greater Prairie-Chickens